2014
DOI: 10.1051/0004-6361/201322450
|View full text |Cite
|
Sign up to set email alerts
|

Mass, velocity anisotropy, and pseudo phase-space density profiles of Abell 2142

Abstract: Aims. We aim to compute the mass and velocity anisotropy profiles of Abell 2142 and, from there, the pseudo phase-space density profile Q(r) and the density slope − velocity anisotropy β − γ relation, and then to compare them with theoretical expectations. Methods. The mass profiles were obtained by using three techniques based on member galaxy kinematics, namely the caustic method, the method of dispersion-kurtosis, and MAMPOSSt. Through the inversion of the Jeans equation, it was possible to compute the velo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
75
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 70 publications
12
75
3
Order By: Relevance
“…Munari et al (2014) compared several mass estimation methods and concluded that the mass of the cluster is M 200 = 0.875 × 10 15 h −1 M (if recalculated to the Hubble parameter H 0 = 100 h km s −1 Mpc −1 , as used in our paper); this value is 0.965 times lower than the dynamical mass of A2142 as calculated in Tempel et al (2014b). This shows that the masses in Tempel et al (2014b) are quite precise.…”
Section: Abell Cluster A2142mentioning
confidence: 52%
“…Munari et al (2014) compared several mass estimation methods and concluded that the mass of the cluster is M 200 = 0.875 × 10 15 h −1 M (if recalculated to the Hubble parameter H 0 = 100 h km s −1 Mpc −1 , as used in our paper); this value is 0.965 times lower than the dynamical mass of A2142 as calculated in Tempel et al (2014b). This shows that the masses in Tempel et al (2014b) are quite precise.…”
Section: Abell Cluster A2142mentioning
confidence: 52%
“…The red curve indicates the mass profile inferred from spectroscopic X-ray measurements (Ettori et al 2010). The symbols indicate the values of M 200 calculated from weak gravitational lensing (pink triangle, Umetsu et al 2009), galaxy kinematics (black triangle, Munari et al 2014) and Suzaku X-ray (green square, Akamatsu et al 2011) non-thermal energy budget in galaxy clusters; iii) detect infalling gas clumps to study the virialization of infalling halos within the potential well of the main structure.…”
Section: Discussionmentioning
confidence: 99%
“…where M 500 =8.66·10 14 M is the cluster mass at R 500 = 1408 kpc (values derived from Munari et al 2014), f b = Ω b /Ω m = 0.15 is the cosmic baryon fraction, with Ω b the baryon density, Ω m the matter density, and h(z) = Ω m (1 + z) 3 + Ω Λ the ratio of the Hubble constant at redshift z to its present value.…”
Section: Entropy Profilementioning
confidence: 99%
“…This cluster belongs to the sample selected in the framework of the XMM Cluster Outskirts Project (X-COP), a Very Large Program on XMM-Newton which aims at studying the outskirts of an SZ-selected sample of 13 massive, nearby clusters. Abell 2142 is a massive cluster (M 200 ∼ 1.3 × 10 15 M , Munari et al 2014) at a redshift of 0.09 (Owers et al 2011). The cluster hosts a moderate cool core (K 0 = 68 keV cm 2 , Cavagnolo et al 2009) and exhibits multiple concentric cold fronts in its central regions (Markevitch et al 2000;Rossetti et al 2013), which are indicative of ongoing sloshing activity extending out to 1 Mpc from the cluster center (Rossetti et al 2013).…”
Section: Introductionmentioning
confidence: 99%